2013
DOI: 10.1371/journal.pone.0073545
|View full text |Cite
|
Sign up to set email alerts
|

Geometry-Driven Cell Organization Determines Tissue Growths in Scaffold Pores: Consequences for Fibronectin Organization

Abstract: To heal tissue defects, cells have to bridge gaps and generate new extracellular matrix (ECM). Macroporous scaffolds are frequently used to support the process of defect filling and thus foster tissue regeneration. Such biomaterials contain micro-voids (pores) that the cells fill with their own ECM over time. There is only limited knowledge on how pore geometry influences cell organization and matrix production, even though it is highly relevant for scaffold design. This study hypothesized that 1) a simple geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 46 publications
3
56
0
Order By: Relevance
“…Supplemented, soluble ECM biopolymers may also bind to integrin receptors without being integrated within matrix assemblies, thus resulting in shielding of the receptor as another potential reason for less effective matrix remodeling. Our findings seem furthermore in line with results reported by Joly et al [47] which showed that tissue growth in a 3D space requires spreading of cells in combination with formation and remodeling of ECM fibers.…”
Section: Discussionsupporting
confidence: 93%
“…Supplemented, soluble ECM biopolymers may also bind to integrin receptors without being integrated within matrix assemblies, thus resulting in shielding of the receptor as another potential reason for less effective matrix remodeling. Our findings seem furthermore in line with results reported by Joly et al [47] which showed that tissue growth in a 3D space requires spreading of cells in combination with formation and remodeling of ECM fibers.…”
Section: Discussionsupporting
confidence: 93%
“…Cells adopt an elongated chord-like appearance, as we reported earlier [44], owing to the balance of contractile actomyosin forces and substrate geometry [34,55]. Moreover, the change of cellular behaviour around pore closure compares with that described in a study showing the relevance of the geometrical model in smaller pores [56] ( figure 1f ). Also, the continuous actin band forming parallel to the tissue-medium interface is reminiscent of the actin ring observed in other contexts of tissue growth, such as wound healing [57].…”
Section: Discussionsupporting
confidence: 72%
“…[65] Accordingly, the macroporous hydrogel provides heterogeneous physical structure signals to the cells, a cue with a tremendous impact on cell growth (e.g., void filling) independent of the initial pore size. [66] …”
Section: Microstructured Gag Gels Nanoparticle-containing Gag Gelmentioning
confidence: 99%